2019
DOI: 10.1186/s12968-019-0527-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of aortic valve 4D flow analysis and myocardial deformation by cardiovascular magnetic resonance in patients after the arterial switch operation

Abstract: BackgroundAortic regurgitation (AR) and subclinical left ventricular (LV) dysfunction expressed by myocardial deformation imaging are common in patients with transposition of the great arteries after the arterial switch operation (ASO). Echocardiographic evaluation is often hampered by reduced acoustic window settings. Cardiovascular magnetic resonance (CMR) imaging provides a robust alternative as it allows for comprehensive assessment of degree of AR and LV function. The purpose of this study is to validate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Various clinical studies have shown that EPI factor 5 can provide acceleration with acceptable scanning time in combination with acceptable accuracy, especially when the acquisition volume can be planned with readout and blip phase‐encoding gradient both perpendicular to the main flow direction. 12 , 13 , 30 , 31 , 32 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various clinical studies have shown that EPI factor 5 can provide acceleration with acceptable scanning time in combination with acceptable accuracy, especially when the acquisition volume can be planned with readout and blip phase‐encoding gradient both perpendicular to the main flow direction. 12 , 13 , 30 , 31 , 32 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, implementations of 4DEPI in volunteers and patients with various cardiac diseases with up to moderate valve regurgitation have proven to be of clinical value. 12 , 13 , 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations